Slavery & the invention of Dutch art - Fowler, Caroline O. 1981- (Duke University Press, 2025)
Caroline Fowler examines the fundamental role of the transatlantic slave trade in the production and evolution of seventeenth-century Dutch art.
Bevorzugte Informationsquelle Landingpage (Duke), da weder Titelblatt noch Impressum vorhanden